2020
DOI: 10.1007/s40831-020-00263-w
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Stabilization of Ladle Furnace Slag with Different Additives

Abstract: Ladle furnace slag disintegrates into fine powder during cooling due to phase transformations of di-calcium silicate. This creates an adverse impact on working conditions and the environment by dust generation. In this paper, a short overview on different studies to overcome the disintegration problem is provided. An attempt was also made to study the effects of several different additives and their mixtures on disintegration of slag. Phase equilibria calculations were carried out for some additives using Fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Samples 1.1 and 2.1 display opposite cracking behavior, despite both capturing significant amounts of Si in C2AS. Small concentrations of various oxides have proven to have a stabilizing effect by forming solid solutions with C2S [28]. A recent study found that the addition of up to 3% of TiO 2 effectively stabilized the β-polymorph by substituting Si 4+ in the SiO 4 2− tetrahedron with Ti 4+ [29].…”
Section: Slag Characteristics and Leachingmentioning
confidence: 99%
“…Samples 1.1 and 2.1 display opposite cracking behavior, despite both capturing significant amounts of Si in C2AS. Small concentrations of various oxides have proven to have a stabilizing effect by forming solid solutions with C2S [28]. A recent study found that the addition of up to 3% of TiO 2 effectively stabilized the β-polymorph by substituting Si 4+ in the SiO 4 2− tetrahedron with Ti 4+ [29].…”
Section: Slag Characteristics and Leachingmentioning
confidence: 99%
“…In the past few years, many scholars presented the elemental analysis of LS using X-ray fluorescence (XRF) and found that the types and quantities of LS were not all the same. Nevertheless, the main chemical compositions of LS are similar, as shown in Table 2.1 (Adesanya et al 2017a(Adesanya et al , 2017b(Adesanya et al , 2020Adolfsson et al 2011;Bocci 2018;Gijbels et al 2020;Gollapalli et al 2020;Manso et al 2005;Moliné et al 2018;Monkman et al 2009;Montenegro et al 2012;Murri et al 2013;Papayianni and Anastasiou 2012;Pinheiro et al 2020;Rađenović et al 2013;Salman et al 2015;Setié n et al 2009;Shi 2002;Skaf et al 2016;Tossavainen et al 2007;Yildirim and Prezzi 2017).…”
Section: Chemical Compositionmentioning
confidence: 76%
“…The heavy metals in LS are also detected in several studies. From Table 2.3, MnO, Cr2O3, and ZnO are the main detected heavy metal oxides (Adesanya et al 2020;Adolfsson et al 2011;Bignozzi et al 2013;Bocci 2018;Gijbels et al 2020;Gollapalli et al 2020;Herrero et al 2016;Rađenović et al 2013;Salman et al 2015;Setié n et al 2009;Shi 2002;Tossavainen et al 2007;Yildirim and Prezzi 2017).…”
Section: Nm-not Mentionedmentioning
confidence: 98%
See 2 more Smart Citations